Orta Asya’da Enerji Politikaları ve Küresel Rekabet Bağlamında Türkiye’nin Rolü Üzerine Bir Değerlendirme - Bahar ÖZSOY; Esra Banu SİPAHİ; Yusuf SAYIN (Gazi Akademik Bakış)
In today’s international relations system, energy -especially oil and natural gas- is one of the most discussed issues. The countries that have these two important energy sources can be targeted by imperialist global energy actors and remain defenseless against them. One of the prominent regions in the world in terms of oil and natural gas reserves is the Central Asia in which the countries are faced with the mentioned risks. At this point, the main priority for these countries is to protect themselves from this competition as much as possible by taking lessons from such as countries Iraq, Iran, and Venezuela that are targeted by global powers and to realize their potential to achieve higher level of income and welfare. Recently, the energy issue that has been risen to the top of Turkey’s agenda with Turkish natural gas and oil exploration endeavors on the Black Sea and the Mediterranean Sea and with the war between Russia and Ukraine, stands out as the main factor to redefine regional and global relations. At this point, energy can be seen as an important element to improve relations between the countries of Turkic origin in the Central Asia and Turkey. This study, prepared based on the basic assumption that the unifying element between the Turkic states can be “energy”, focuses on the potential of energy cooperation to limit the global competition.